Faktor-Faktor yang Mempengaruhi Alokasi Belanja Pendidikan pada Dinas Pendidikan Aceh Jaya - Zari Marfit; Dewi Sartika; Rimal Mahdani; Cut Sri Firman Hastuti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the factors influencing the allocation of education expenditure at the Education Office of Aceh Jaya Regency. In Indonesia, regional governments are required to allocate at least 20% of the Regional Revenue and Expenditure Budget (APBD) to education, excluding educators’ salaries and official education expenses, to improve access to and the quality of education. Aceh Jaya Regency depends heavily on intergovernmental transfers, including the Aceh Special Autonomy Fund (DOK), the Special Allocation Fund (DAK), and the General Allocation Fund (DAU), whose fluctuations may affect education budget allocation. This study employs a descriptive quantitative approach using secondary data obtained from the budget realization reports of the Education Office for the 2010–2024 fiscal years. Data were analyzed using multiple linear regression. The findings indicate that, partially, the Aceh Special Autonomy Fund (DOK), the Special Allocation Fund (DAK), and the General Allocation Fund (DAU) each have a significant effect on the allocation of education expenditure. Simultaneously, these three funding sources have a positive and significant influence on education expenditure allocation, with significance values below 0.05. Therefore, the study concludes that DOK, DAK, and DAU jointly play an important role in determining education expenditure allocation in Aceh Jaya Regency, supporting the acceptance of the proposed hypothesis (H4).